A new plesiosaur (Reptilia: Sauropterygia) specimen from the upper cretaceous of west antarctica, with comments on the ontogeny and morphological diversity of the elasmosaurid pelvic girdle - Miller, Case V.; O'Gorman, José P.; Salisbury, Steven W.; Coria, Rodolfo Anibal; Roberts, Eric M.; O’Connor, Patrick M.; Reguero, Marcelo Alfredo; Lamanna, Matthew C.
Although knowledge of Mesozoic marine reptiles from Antarctica has improved considerably in recent years, associated and well-preserved skeletal material of these animals remains uncommon. Here we describe a largely complete, closely associated plesiosaur pelvic girdle recovered from the uppermost Cretaceous (Maastrichtian) Sandwich Bluff Member of the López de Bertodano Formation of Vega Island, in the James Ross Basin of the northernmost Antarctic Peninsula. The new specimen exhibits characters that allow its referral to Elasmosauridae, but its incompleteness precludes a more precise taxonomic determination. Ontogenetically variable and systematically useful features of the elasmosaurid pelvis are reviewed and discussed. The new specimen improves knowledge of Southern Hemisphere elasmosaurids just prior to the K/Pg extinction event. Fil: Miller, Case V. University of Hong Kong; Hong Kong Fil: O'Gorman, José P. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Salisbury, Steven W. Carnegie Museum of Natural History; Estados Unidos. The University of Queensland; Australia Fil: Coria, Rodolfo Anibal. Provincia del Neuquén. Municipalidad de Plaza Huincul. Museo "Carmen Funes"; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Roberts, Eric M. James Cook University; Australia Fil: O’Connor, Patrick M. Carnegie Museum Of Natural History; Estados Unidos. Ohio University; Estados Unidos Fil: Reguero, Marcelo Alfredo. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina Fil: Lamanna, Matthew C. Carnegie Museum of Natural History; Estados Unidos